AIEE phenomenon: tetraaryl vs. triaryl pyrazoles. Issue 96 (12th October 2015) - Mukherjee, Sayani; Salini, P. S.; Srinivasan, A.; Peruncheralathan, S.
Abstract : A library of tetraaryl pyrazole derivatives were synthesized and the AIEE phenomenon was explored. Abstract : Tetraarylpyrazoles are synthesized from commercially available materials in three steps and found to exhibit Aggregation Induced Emission Enhancement (AIEE) characteristics. Removing one aryl unit from tetraarylpyrazole leads to Aggregation Caused Quenching (ACQ), thus the number of aryl groups plays an important role in exploring such a phenomenon.